Pelaksanaan Inovasi Pembelajaran PAI pada siswa kelas IX Di SMPN 1 Ngoro - Husni Tamrin; Ahmad Shofiyul Himami; Moh Kholik (Irsyaduna: Jurnal Studi Kemahasiswaaan, 2022)
This study aims to describe the process of implementing PAI learning innovations carried out by PAI teachers so that these innovations make it easier for teachers to convey learning and make it easier for students to accept learning, the problems raised in this study are 1. How do teachers implement method innovations and PAI learning strategies in class IX at SMPN 1 Ngoro. 2. How is the innovation of developing PAI learning evaluation for class IX students at SMPN 1 Ngoro. This study aims to 1. Identify the implementation of innovative PAI learning methods and strategies in class IX at SMPN 1 Ngoro. 2. Identify innovations in the development of PAI learning evaluations for class IX students at SMPN 1 Ngoro. The results of this study are expected to be one of the reference results to make it easier to understand the importance of making PAI learning innovations and be used as reference material for relevant future studies. This research is afield research with a qualitative approach. A qualitative approach is a series of activities or processes of disclosing something that is not yet known by using interviews, observation, documentation method, data analysis, and data validity. Research results in 1. Learning innovation is a continuous change in both methods and learning strategies, as well as taking a special approach to students so that the teaching and learning process and learning objectives can be carried out properly. 2. Innovations in the development of PAI learning evaluations carried out are looking for obstacles and solutions if there are problems so that they do not recur, besides that evaluation must also be carried out from the lesson plan to follow-up. Research conclusions, among others. 1. Implementation of PAI Learning Innovation in Class IX At SMPN 1 Ngoro seen from the different characteristics of students. 2. Learning evaluation must be carried out from the lesson plan to follow-up and carried out in the fairest way possible